A study on the relationship between reward and knowledge sharing among employees in public sector at Beaufort District Council / Dyna Nadia Julkipli - Julkipli, Dyna Nadia (2011)
This study was conducted to identify the relationship between rewards and knowledge sharing among employee in public sector at Beaufort District Council. This study also examined the level of knowledge sharing of the employee in the organization. Besides that it is also to know the pattern of knowledge sharing of the employee in Beaufort District Council. The samples of 60 respondents in Beaufort District Council and various backgrounds were selected to answer the questionnaire in this research. The result of this study shows that there is a relationship between rewards and knowledge sharing in the organization. Besides that, it had been identified that most of government servants shared their knowledge with others especially Support Staff C/D in Beaufort District Council. Moreover, there are no significant differences in age, gender, marital status, service tenure and job position with knowledge sharing in the organization.